VÁZQUEZ GARCÍA, Francisco. (2018). Georges Canguilhem. Vitalismo y Ciencias Humanas. Cádiz: Editorial UCA, 199 páginas. - Delgado Pastor, Diego (Daimon Revista Internacional de Filosofia, 2020)
Recensión de: VÁZQUEZ GARCÍA, Francisco. (2018). Georges Canguilhem. Vitalismo y Ciencias Humanas. Cádiz: Editorial UCA.